Changes in Knowledge About Mothers Stunting Before and After Watching the Video on Mothers of Stunting Toddlers in Puskesmas Anak Air Kota Padang - Yaumil Fauziah Milfa; Fitri Khairani; Annisa Namirah Nasution (Talenta Publisher, 2025)
Background: Stunting is a developmental disorder in children caused by chronic malnutrition and recurrent infections. One effective way to convey information about nutrition to mothers of stunted toddlers is by watching videos. Objective: This study aimed to determine the changes in knowledge of mothers of stunted toddlers before and after watching intervention videos. Methods: A